Copper-catalyzed fragmentation-rearrangement sequence of cycloketoxime esters. Issue 5 (31st January 2020) - Wu, Yixiao; Zhao, Binlin; Shi, Zhuangzhi; Yuan, Yu
Abstract: Copper-catalyzed fragmentation-rearrangement sequence of cycloketoxime esters is reported. This strategy provides direct access to diverse ring-opening acyloxylation nitriles avoiding the use of toxic cyanic reagents with good atom economy and well functional group tolerance. Experimental exploration showed that tetrabutylammonium bromide (TBAB) played an irreplaceable role in this transformation. Based on the primary mechanistic experiments, a plausible mechanism was also proposed. Graphical abstract: Image 1 Highlights: The first copper-catalyzed ortho-alkyl or non-substituted cycloketoximes is achieved affording cyano-containing benzoates. The reaction only requires copper catalyst without addition of oxidant, base, ligand or toxic cyanide reagents. A wide range of cyano-containing benzoates could be obtained under the mild conditions.